Systems change to improve tobacco use identification and referral in the chiropractic setting: a pilot study - Buettner-Schmidt, Kelly (Chiropr Man Therap, 2018)
BACKGROUND: Tobacco use remains a leading cause of death and disability in the United States. Health professionals need to address the use of tobacco products by their patients, but chiropractic clinical systems often remain unsupported and underappreciated in their role to facilitate tobacco use cessation. METHODS: This pilot study tested an intervention to assist a chiropractic community to implement sustainable health systems changes for tobacco use based on U.S. Public Health Service guidelines. Chiropractors were educated on the Ask, Advise, Refer (AAR) approach, provided with ongoing guidance, and followed for six months to assess systems change. The study was conducted from March 2016 to July 2017. RESULTS: Evidence of a systematic process in place to conduct AAR was present in all clinics by the end of the fourth month of the intervention period. Although no clinic had sustained health system change for full AAR, all six of the clinics made progress in the individual AAR components. Furthermore, five clinics achieved sustained system change for the Ask component, as after systems change was achieved, the rate of tobacco user identifications did not drop below 50%. For the Advise component, five clinics succeeded in having individual months of ≥50% of tobacco users being advised, and three clinics achieved the formal definition of systems change. For the Refer component, no clinic achieved system change, although four had individual months of ≥50% of tobacco users being referred. The patient quit rate was 13.3% (n = 15) for the 30-day follow-up and 16.7% (n = 6) for the three-month follow-up. CONCLUSIONS: This study demonstrates the feasibility of implementing a health systems change in the chiropractic setting to identify tobacco users, to advise them to quit, and to refer users for cessation services.